The Potential of Film Analysis for Family Sociology: Methodological Considerations Using the Example of "Das Doppelte Lottchen" - Scholz, Sylka; Kusche, Michel; Scherber, Nicole; Scherber, Sandra; Stiller, David (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2013)
Sociological research has so far largely underestimated the potential of film analysis as a means of analyzing societal change. The findings presented in this article are part of current efforts to establish a visual sociology, and specifically a sociology of film. Based on a research project on the cultural foundations of the family and gender order, the article is centered on the potential contribution of film analysis for sociological enquiry. For this purpose, it introduces research on the films Das doppelte Lottchen ("Two Times Lotte," 1950, director: Josef von BAKY) and its remake Charlie und Louise. Das doppelte Lottchen (1994, director: Joseph VILSMAIER). Both movies are understood as "discursive events" within broader public discourses. Our methodology draws on a sociology of knowledge approach to discourse analysis and takes it further by applying audio-visual methods. Documentary video analysis serves as a particularly important toolkit. The article examines the interpretative options with respect to different ways of private life that these movies discursively offer. Both films deny the widely observed social developments towards a pluralization of ways of private life and support an ideal image of the nuclear family. In the 1950 film, the parents' divorce is considered unacceptable, whereas the 1994 remake takes the separation as the starting point of its narration. This discursive transformation can be interpreted as an institutionalization and normalization of separation and divorce. However, the general cultural principle of an intact and harmonious family is not challenged, but rather discursively updated, affirmed and reproduced. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs1401157